2003
DOI: 10.1097/00006199-200303000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nurse Staffing on Adverse Events, Morbidity, Mortality, and Medical Costs

Abstract: Background: Nurse staffing levels are an important working condition issue for nurses and believed to be a determinant of the quality of nursing care and patient outcomes. Objectives:To examine the effects of nurse staffing on adverse events, morbidity, mortality, and medical costs. Methods:Using two existing databases, the study sample included 232 acute care California hospitals and 124,204 patients in 20 surgical diagnosis-related groups. The adverse events included patient fall/injury, pressure ulcer, adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
300
1
23

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(335 citation statements)
references
References 13 publications
11
300
1
23
Order By: Relevance
“…These problems can often be effectively tackled on a standard ward through proactive patient care led by experienced qualified nursing staff, with prompt access to medical support when required. Adequate staffing of surgical wards with qualified nurses may improve patient safety [28,29] and reduce the incidence of pneumonia, surgical site infection, and postoperative sepsis [30][31][32]. Hospitals with higher nurse staffing levels may also be more cost-effective in terms of postoperative outcomes (lower mortality with similar costs), especially for high-risk surgical patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…These problems can often be effectively tackled on a standard ward through proactive patient care led by experienced qualified nursing staff, with prompt access to medical support when required. Adequate staffing of surgical wards with qualified nurses may improve patient safety [28,29] and reduce the incidence of pneumonia, surgical site infection, and postoperative sepsis [30][31][32]. Hospitals with higher nurse staffing levels may also be more cost-effective in terms of postoperative outcomes (lower mortality with similar costs), especially for high-risk surgical patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies found a significant association in the opposite direction, with units M a n u s c r i p t / hospitals with more staff having higher rates of pressure ulcers (Cho et al, 2003, Twigg et al, 2013. Nine studies explored associations with drug administration errors of which three showed low staffing to be significantly associated with higher rates of errors (Frith et al, 2012, Patrician et al, 2011.…”
Section: Other Outcomesmentioning
confidence: 99%
“…A number of these studies found an association between a nursing skill mix that has a higher proportion of RNs and better outcomes including lower mortality / failure to rescue (Blegen et al, 2011, Estabrooks et al, 2005, lower rates of infections (Blegen et al, 2011, Cho et al, 2003, McGillis Hall et al, 2004, falls (Blegen and Vaughn, 1998, Donaldson et al, 2005, Patrician et al, 2011, pressure ulcers (Blegen et al, 2011, Ibe et al, 2008, and higher patient satisfaction (Potter et al, 2003). The overall pattern of results is largely consistent, with the only significant contradictory evidence coming from one of the weaker studies which showed that a higher proportion of registered nurses was associated with a higher nurse reported incidence of pneumonia (Ausserhofer et al, 2013).…”
Section: March 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…This constituted a considerable saving compared to the cost of thrombolytic therapy in acute myocardial infarction at US$182 000 per life saved or routine cervical cancer screening at a cost of US$432 000 per life saved. Similarly, Cho 26 has found the costs of hospital-acquired pneumonia to be US$22 390-$28 505 per episode. These studies [23][24][25][26] clearly support the proposition that to increase RN hours of care is cost effective as it improves patient outcomes but is also affordable.…”
Section: Affordability Of Additional Rn Staffingmentioning
confidence: 96%